Managing span of control efficiency and effectiveness: a case study. Issue 7 (3rd October 2016) - El-Khalil, Raed; El-Kassar, Abdul-Nasser
Abstract : Purpose: The purpose of this paper is to address the following issues: first, the significance of the three independent variables (the chassis, trim, and assembly departments) on the three outputs (direct run loss first time capability, jobs per hour (JPH) lost, and injury rate); second, the optimal level of span of control based on the best achieved outputs; and third, whether increasing the span of control post 2009 improved manufacturing outputs in comparison with a span of control pre 2009. Design/methodology/approach: The optimal level of span of control at the automotive Big Three (Chrysler LLC, Ford, General Motors) is investigated using design of experiments. Findings: The analysis shows that the variables are significant for all outputs, except for chassis on injury. All three variables deteriorate as the span of control increases. The paper indicates that the lower the span of control the better the output variables. Originality/value: Based on the recommendations given by the managers at the Big Three facilities visited, the top three variables that were utilized from the assembly facilities for this study are the span of control at the Chassis, Trim, and Assembly departments, and the outputs are Direct Run Loss First Time Capability, JPH Lost, and Injury Rate.